Remote sensing applications for monitoring restoration outcomes in boreal forestry-drained peatlands : Reviewed applications and future potential - Ikkala, Lauri; Ismail,.; Wolff, Franziska; Marttila, Hannu; Ronkanen, Anna-Kaisa; Alekseychik, Pavel; Rana, Parvez; Kohv, Marko; Tahvanainen, Teemu; Tolvanen, Anne; Haghighi, Ali Torabi; Kumpula, Timo; et al. (Elsevier, 2026)
Peatland restoration can halt biodiversity loss and organic soil degradation and mitigate climate change. Monitoring of restoration impacts requires novel approaches that can be scaled to large site networks. On a smaller scale, the restoration practitioners would likewise benefit from spatially and temporally comprehensive and objective monitoring data. This narrative review compiles potential remote sensing methods for practical monitoring of the ecohydrological processes in restoration of forestry-drained boreal peatlands to support and complement conventional ground monitoring approaches that are restricted by spatial coverage. Remote sensing provides tools for tracking the changes in soil surface moisture, water flow routes, vegetation cover and structure, topography, peat depth and greenhouse gas emissions. We emphasize that the suitable indicators of restoration success, platforms and sensors should be tailored to specific restoration cases with their own initial site conditions and restoration targets. The choice of spatial and temporal resolutions of data is defined by the scale and change rate of the restoration indicators. Data acquisition campaigns and selection of existing datasets require meticulous planning due to seasonal changes in hydrology and vegetation. We also compiled practical experiences on selecting remote sensing tools and ensuring satisfactory data quality to facilitate the implementation of remote-sensing-based monitoring. Finally, we provide recommendations on how the rapid development of remote sensing technology, encompassing new uncrewed applications and novel sensors on conventional platforms, can offer a range of monitoring tools to cater to the growing needs for spatially comprehensive data amounts assessing peatland restoration success in boreal conditions.
Keywords: peatland; restoration; rewetting; revegetation; UAS; airborne; satellite